A randomized controlled trial to assess safety and efficacy between terminal chop, stop and chop, and direct chop - Aprajita Sinha; Arvind Kumar Morya; Vinita Gupta; Ripunjay Prasad (Indian Journal of Ophthalmology, 2023)
Purpose: The goal in developing new techniques of cataract surgery is to provide a safer, more efficient surgical experience with the lowest complication rate and endothelial cell loss. We compared the efficiency and safety of stop-and-chop, direct chop, and the novel terminal chop techniques of nuclear fragmentation for cataracts grade II-V. Methods: We conducted a prospective randomized clinical trial comparing three different techniques of phacoemulsification, namely, stop-and-chop, direct chop, and terminal chop to assess any differences between them and to establish whether any one method was superior to the others. The pre- and postoperative parameters studied, included central corneal thickness (CCT), ultrasonic time (UST), endothelial cell density (CD), cell loss and effective phacoemulsification time (EPT), average cumulative dissipative energy (CDE), and best-corrected visual acuity, among others. Results: 307 eyes were recruited to the study, 102 were recruited to the stop-and-chop group, 103 to the direct chop group, and 102 to the terminal chop group. Statistical differences were found between the techniques with regard to postoperative CCT among NS II (P. 0001) and NS IV cataracts (P = .005) with the lowest values in the terminal chop group among NS II, NS III, and NS IV cataracts. Endothelial cell loss was minimum with a terminal chop in NS II (P = .018) and NS IV cataracts (P = .245). CDE was minimum in terminal chop across different cataract densities. Conclusion: Terminal chop showed improvement over the other two techniques in terms of CDE and was comparable to them with regard to other parameters.